The relevance of ECOWAS in the 21st century: questioning good governance and political stability - Mathebula, N. E. (International Conference on Public Administration and Development Alternatives (IPADA), 2017)
The Economic Community of West African States (ECOWAS) is a 15 member nations of the West African states founded in 1975 for primarily promoting economic integration and good governance. This paper interrogates through literature review and secondary sources the relevance of the ‛Community’ in the 21st century. The paper argues that with socio-economic and politico-legal turmoil by some of the member states, ECOWAS continues to lose its relevance and executing the objectives it was initially founded for. West African states are marked with political instability, humanitarian crimes, civil unrest, corruption, poor or bad governance and lack of transport and communication infrastructures. This paper therefore calls for self-reflection and introspection of ECOWAS if economic integration and good governance are to be achieved. This will not only be for the benefit of the ‛Community’ and its region but also that of the African continent in general. Using the Kingdon’s Multiple Streams Theory, the paper probe challenges and possible solutions as confronting ECOWAS.
Journal article, Published in International Conference on Public Administration and Development Alternatives (IPADA), The 2nd Annual Conference on ‛‛ The Independence of African States in the Age of Globalisation”, July 26-28, 2017
Keywords: ECOWAS; Economic integration; Good governance; Kingdon’s Multiple Streams Theory; Political stability; Africa, West -- Economic integration